Analyzing the situation of municipal solid waste in Amman City using small cell areas - Aymen Awad (Case Studies in Chemical and Environmental Engineering)
This study aims to investigate the solid waste situation in Amman City. Amman is the capital of Jordan with 3 million people. The rates of solid waste generation, its composition, and the types and quantities of solid waste were all investigated. These parameters were tested against families’ members, sites in different locations, monthly income, and seasonal time. Results could be used as key solution for Jordanian solid waste landfills problems and for future improvements. Four locations with different sites at a distance of 20 km from the city center were selected to do the investigations during the period started from September 2022 until August 2023. It was found that the average solid waste generation rate ranged from 0.6 to 1 kg/capita/day. The solid waste types and compositions were found typically similar to compositions of solid waste generated in most world countries. The average percent compositions of solid waste generated in the city were as follows: 63 % organic waste which represented the large portion of solid waste composition, 13.5 % plastic waste, 14.8 % paper waste, 3.2 % metal waste, 2.6 % glass waste, and the remaining 2.9 % was miscellaneous rubbish. Findings also reflected the current situation of solid waste landfills serving the city. Results recommend that most of the Jordanian landfills have to be rehabilitated and maintained according to the estimate solid waste generation rates, contents, types, and quantities. Results indicated that the city needs to construct an effective solid waste management plan for the city in future.